A patient blood management perspective on Anemia in the obese patient journey - Duarte, Gustavo de Carvalho; Wei, Wenhua; Cho, Gavin (Frontiers in Anesthesiology, 2023)
Obesity and anemia are increasing prevalence around the globe. They can interplay and are both associated with high morbidity and poorer clinical outcomes. Inflammation and iron deficiency are important contributors to anemia in obese patients. Furthermore, obesity surgery can trigger high blood loss, increased demand for blood transfusions and long-term nutrient deficiency. Patient blood management programs have been crucial in improving patients’ clinical results whilst minimizing costs in many different settings, such as orthopedic surgery, cardiovascular surgery, pregnancy and intensive care unit patients. In this mini-review, we will discuss applications of patient blood management principles in caring obese individuals during the patient journey.